1999
DOI: 10.1142/s0192415x99000033
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Pulse Rate and Skin Temperature Evoked by Electroacupuncture Stimulation with Different Frequency on both Zusanli Acupoints in Humans

Abstract: The purpose of this study was to investigate the effect of electroacupuncture stimulation (EA) of different frequency on pulse rate and skin temperature. Sixteen healthy male medical student volunteers received EA of 2 Hz, and 100 Hz, respectively on the both Zusanli acupoints (St-36) while resting. Their pulse rates were measured on the middle finger, and skin temperature was taken between the thumb and index finger before, during, and after EA stimulation. Each test took 35 minutes. The initial 10 min were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Hsieh et al tested the effects of low-frequency (2 Hz) and high-frequency (100 Hz) EA stimulation at the ST-36 acupoint on heart rate and skin temperature in humans and found that high-frequency EA stimulation led to a reduction in heart rate by activating parasympathetic nerves [14]. Thus, we hypothesized that the cholinergic nerves are involved in enhancing exogenous insulin sensitivity in a STZ-induced diabetic rat model.…”
Section: Introductionmentioning
confidence: 97%
“…Hsieh et al tested the effects of low-frequency (2 Hz) and high-frequency (100 Hz) EA stimulation at the ST-36 acupoint on heart rate and skin temperature in humans and found that high-frequency EA stimulation led to a reduction in heart rate by activating parasympathetic nerves [14]. Thus, we hypothesized that the cholinergic nerves are involved in enhancing exogenous insulin sensitivity in a STZ-induced diabetic rat model.…”
Section: Introductionmentioning
confidence: 97%
“…Zhao used the lymphocyte transformation test (LTT) and measured interlukin-2 (IL-2) activity to evaluate whether the EA-induced immune system regulatory effects are due to the release of Ach by parasympathetic nerves [17]. Hsieh et al tested the effects of low frequency (2 Hz) and high frequency (100 Hz) EA stimulation at the ST-36 acupoint on heart rate and skin temperature in humans and found that high-frequency EA stimulation led to a reduction in heart rate by activating parasympathetic nerves [18]. Previous studies have shown that EA has plasma glucose lowering effects in non-insulin-dependent types; however, the plasma glucose lowering effects and the mechanisms by which EA induces a hypoglycemic effect in insulin-dependent types is not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Post-stroke-onsetinsomnia is mainly caused by anxiety resulting from hyperactivity of the sympathetic nervous system (Palomaki et al, 2003;Leppavuori et al, 2002). Based on the hypothesis that acupuncture could control the autonomic nervous system (Baba et al, 2002;Kotani et al, 2001;Haker et al, 2000;Suter and Kistler, 1999;Hsieh et al, 1999;Knardahl et al, 1998), a RCT (Randomized Controlled Trial) was conducted by authors in a previous study, and based on those results, which was reported in the American Journal of Chinese Medicine that intradermal acupuncture on Shen-Men (He-7) and Nei-Kuan (EH-6) acupoints improved insomnia after stroke (Kim et al, 2004). In that report, the results were attributed to the inhibitory effects of Shen-Men and Nei-Kuan on sympathetic activity, however, the direct variables related to the subjects' autonomic nervous function were not assessed.…”
Section: Introductionmentioning
confidence: 99%